(untitled) (Revista horizonte, 2021)
In 2010, in Chile the Ministry of Education (MINEDUC) in conjunction with the National Sports Institute (IND) applied for the first time the quality measurement system (SIMCE), in Physical Education, which consists of measuring of the students’ physical fitness, considering five aspects: anthropometry, aerobic power, muscular strength-endurance, elastic-reflex strength, and hamstring-lumbar movielasticity. Objective: To analyze the physical condition and anthropometric measurements of the students of municipal schools of the ValparaÃso Commune and the Juan FernÃ¡ndez Archipelago, between the years 2015 and 2016. Method: Descriptive and comparative study developed under a quantitative paradigm. 71 students from Juan FernÃ¡ndez and 521 from the ValparaÃso commune (245 men and 276 women) participated. Weight, height, waist circumference, 4 skinfolds were measured; Long jump on foot together, Flexo-Extensions of elbows in 30 seconds, Abdominal Dynamic Resistance Force in 1 minute and Hamstring-Lumbar Movielasticity and Aerobic Power. Results: The findings indicate that there is no significant difference (pâ‰¤0.05) in any of the measured variables, but when grouped in accumulated percentages by category, the measures favor the island students of Juan FernÃ¡ndez. The results allow to alert the authorities responsible for educational and health organizations in Chile to design and correct existing public policies with the purpose of helping to promote school health in Chile.